Nikāh Sirri and Its Impact: The Perspective of Maqashid Ash-Shari’ah of Imam Asy-Syathiby - Fanani, Zainal (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2024)
Background. The legal status of nikāh sirri (secret or unregistered marriage) is controversial because it is not announced and not officially recorded. The views of scholars on secret marriage and the factors causing it, as well as the legal regulations in force in Indonesia, need to be studied. Aim. Examines nikāh sirri from the perspective of maqāṣid asy-syari’ah, which includes five essential goals of Islamic law: the maintaining religion (hifẓ ad-dīn), soul (hifẓ an-nafs), descendants (hifẓ an-nasl), property (hifẓ al-māl), and reason (hifẓ al-’aql). Method. This research utilizes a literature review with a descriptive-analytical approach to Islamic jurisprudence and relevant regulations. Result. Nikāh sirri causes more harm (mafsadat) than benefit (maslahat), particularly concerning the rights of wives and children in inheritance, financial support, and legal protection. Based on maqāṣid asy-syari’ah, nikāh sirri is considered impermissible (haram) due to its adverse effects on mental well-being, economic instability, and threats to legitimate lineage. The formal registration of marriage is crucial for ensuring the protection of family rights.